CFD investigation of a core-mounted-target-type thrust reverser, Part 2: reverser deployed configuration - Mahmood, Tashfeen; Jackson, Anthony J. B.; Sethi, Vishal; Khanal, Bidur; Fakhre, Ali (ASME, 2017)
CMTTTR design was proposed by NASA in the second half of the 90's. NASA carried out several experiments at static conditions, and their acquired results suggested that the performance characteristics of the CMTTTR design falls short to comply with the mandatory TR performance criteria, and were therefore regarded as an infeasible design. However, the authors of this paper believe that the results presented by NASA for CMTTTR design require further exploration to facilitate the complete understanding of its true performance potential. This Part2 paper is a continuation from Part1and presents a comprehensive three-dimensional (CFD) analyses of the CMTTTR in deployed configuration; the analyses at forward flight conditions will be covered in Part 3. The key objectives of this paper are: first, to validate the acquired CFD results with the experimental data provided by NASA: this is achieved by measuring the static pressure values on various surfaces of the deployed CMTTTR model. The second objective is to estimate the performance characteristics of the CMTTTR design and corroborate the results with experimental data. The third objective is to estimate the Pressure Thrust (i.e. axial thrust generated due to the pressure difference across various reverser surfaces) and discuss its significance for formulating the performance of any thrust reverser design. The fourth objective is to investigate the influence of kicker plate installation on overall TR performance. The fifth and final objective is to examine and discuss the overall flow physics associated with the thrust reverser under deployed configuration.
Keywords: Design